ACTION VERBS-BASED TO ACCUSTOM PROCEDURES TEXT - Ranta Butarbutar; Titik Budi Ningsih (Universitas Musamus, 2018)
Action verb has significant effect on pupil’s writing skills of procedures text. This study aims to investigate the use of action verbs at improving pupil’s in writing skill and procedures texts in particularly. Describing of the pupil’s difficulties in writing procedures text, and investigating the effectiveness of action verbs to build up pupils’ ability in writing procedures is the objective of this study. Result figured out that action verbs in writing procedures texts has significantly effect at improving pupils’ ability. Cycle 1showed 60.45 and cycle 2 showed 80.50. Furthermore, the average This study concluded that action verbs in writing skills of procedures text can be suggested as an additional solution for the pupils, teachers, education practitioner, and polish maker to whom with enrich their writing skills on procedures text. It is implied that learning procedures text easier after they asked for difficulties in the beginning of class. And, by using this technique, pupils felt easier to express their opinion and write procedures text. Keywords: action verbs; writing skill; procedures text